Measuring Multimorbidity: Selecting the Right Instrument for the Purpose and the Data Source. Issue 8 (11th August 2021) - Suls, Jerry; Bayliss, Elizabeth A.; Berry, Jay; Bierman, Arlene S.; Chrischilles, Elizabeth A.; Farhat, Tilda; Fortin, Martin; Koroukian, Siran M.; Quinones, Ana; Silber, Jeffrey H.; Ward, Brian W.; Wei, Melissa; et al.
Abstract : Background: Adults have a higher prevalence of multimorbidity—or having multiple chronic health conditions—than having a single condition in isolation. Researchers, health care providers, and health policymakers find it challenging to decide upon the most appropriate assessment tool from the many available multimorbidity measures. Objective: The objective of this study was to describe a broad range of instruments and data sources available to assess multimorbidity and offer guidance about selecting appropriate measures. Design: Instruments were reviewed and guidance developed during a special expert workshop sponsored by the National Institutes of Health on September 25–26, 2018. Results: Workshop participants identified 4 common purposes for multimorbidity measurement as well as the advantages and disadvantages of 5 major data sources: medical records/clinical assessments, administrative claims, public health surveys, patient reports, and electronic health records. Participants surveyed 15 instruments and 2 public health data systems and described characteristics of the measures, validity, and other features that inform tool selection. Guidance on instrument selection includes recommendations to match the purpose of multimorbidity measurement to the measurement approach and instrument, review available data sources, and consider contextual and other related constructs to enhance the overall measurement of multimorbidity. Conclusions: The accuracy of multimorbidity measurement can be enhanced with appropriate measurement selection, combining data sources and special considerations for fully capturing multimorbidity burden in underrepresented racial/ethnic populations, children, individuals with multiple Adverse Childhood Events and older adults experiencing functional limitations, and other geriatric syndromes. The increased availability of comprehensive electronic health record systems offers new opportunities not available through other data sources.